Who gives a hoot? - Kelly, Jacqueline (Kelly, Jacqueline. Calpurnia Tate, girl vet., 2017)
Calpurnia and her grandfather rescue a barn owl from the river and, with the help of Dr. Pritzker, dead mice, and some detective work, nurse it back to health.